2010
DOI: 10.1007/s00246-010-9695-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stents Ameliorate Pulmonary Vein Stenotic Changes in Pigs In Vivo

Abstract: The outcome of stent implantation for pulmonary vein stenosis (PVS) in children remains poor. Several reports describe placing drug-eluting stents to treat PVS, but their effectiveness remains unknown. In this study, three bare-metal stents (BMSs) and three sirolimus-eluting stents (SESs) were implanted in 1-month-old pigs. The pigs were killed 8 weeks later to compare in-stent stenosis rates. The extent of neointimal thickness, as measured by injury score, was significantly less in the SES group than in the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In an animal model with small pulmonary veins, DES were shown to develop less initial proliferation than BMS. 28 Balasubramanian et al 3 found that acute relief of PVS was possible with BMS implantation, however long-term vessel patency and patient survival were poor. Larger stent diameters were associated with longer freedom from restenosis and reintervention in that study.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model with small pulmonary veins, DES were shown to develop less initial proliferation than BMS. 28 Balasubramanian et al 3 found that acute relief of PVS was possible with BMS implantation, however long-term vessel patency and patient survival were poor. Larger stent diameters were associated with longer freedom from restenosis and reintervention in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vein stenosis is defined as the reduction in the total diameter of pulmonary veins more than 50% from the diameter present before the ablation [7]. It results from the radiofrequency energy delivered at the ostia or within the lumen of pulmonary veins [8][9][10]. Ernest et al reported thickening of venous walls from myoblast proliferation and luminal sclerosis of veins characteristic of venous occlusive syndrome secondary to radiofrequency [11].…”
Section: The Lungmentioning
confidence: 99%
“…The rate of restenosis was found to be 47 to 61% in the case of balloon dilation alone whereas in the case of stent deployment, it has shown a significant decrease ranging from 0 to 47% [8,35]. Drug eluting stents are an option but more studies are needed to determine the efficacy and safety of the stents for treating PVS/PVO [9,36]. There is no role for stents in the treatment of PH when PVS is absent.…”
Section: Treatmentmentioning
confidence: 99%
“…According to a previous report by Furukawa et al on the use and effectiveness of drug-eluting stent for PVS, comparison of similar sized drug-eluting stent and bare-metal stent in pigs indicated that bare-metal stent was associated with more severe internal proliferation and stent stenosis and a significantly larger amount of granuloma formation than drug-eluting stent. 21 Drug-eluting stents used in our study were all of the size 3.5 mm. A drug-eluting stent has an advantage of pharmacological benefits; however, we selected a bare-metal stent because the larger stent is believed to be more important for good outcomes.…”
mentioning
confidence: 99%